Circulation Influence On Cloudiness In Poznań - Szyga-Pluta, Katarzyna (Quaestiones Geographicae, 2015)
The frequency of occurrence of cloud cover was analysed taking into consideration its circulation-related conditioning. The atmospheric circulation types according to Osuchowska-Klein (1978) classification were used. The study was made based on diurnal climatological observations carried out in Poznań-Ławica in years 1966–1998. It was found that the cloudless skies and small cloudiness were associated with anticyclonic types of atmospheric circulation and the east macrotype. Moderate cloudiness occurred equally at cyclonic and anticyclonic circulation types. Larger cloud coverage of the sky was associated with cyclonic circulation, especially with the west macrotype.